2012
DOI: 10.1097/bsd.0b013e3182159776
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Facet Load Changes in Adjacent Segments due to Moderate and Severe Degeneration in C5-C6 Disc

Abstract: Higher changes in facet loads along the posterior spinal column may contribute to altered biomechanics in neighboring segments. Future biomechanical experiments are required to develop a more clear understanding of the posterior facet joints response in neighboring segments because of degeneration in a cervical disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…As indicated in the present finite element study, ACDF impairs normal cervical biomechanics, alters mechanics at adjacent segments, resulting in higher stress and hypermobility in adjacent segments. Our results are in line with the reported data of the biomechanical studies on the behavior of the adjacent segments in the setting of different operation procedures [49][50][51][52][53]. Both the present and all of the reported results suggested that ASD might be related to iatrogenic biomechanics.…”
Section: Discussionsupporting
confidence: 92%
“…As indicated in the present finite element study, ACDF impairs normal cervical biomechanics, alters mechanics at adjacent segments, resulting in higher stress and hypermobility in adjacent segments. Our results are in line with the reported data of the biomechanical studies on the behavior of the adjacent segments in the setting of different operation procedures [49][50][51][52][53]. Both the present and all of the reported results suggested that ASD might be related to iatrogenic biomechanics.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to simulation methods reported by Hussain et al [ 25 ], the FE model of the degenerative cervical spine was generated based on the developed FE model of the normal cervical spine. The cervical disc herniation (herniated on the left side) was simulated in C5-6 spinal motion segment.…”
Section: Methodsmentioning
confidence: 99%
“…The cervical disc herniation (herniated on the left side) was simulated in C5-6 spinal motion segment. The changes in geometry and material properties ( Table 2 ) used to simulate the degeneration were adapted from the clinical classification of degeneration of the cervical spine and the results of the previously published literature [ 18 , 25 , 26 ]. For the herniated disc of C5-6, the left posterolateral annulus was weakened as mid-then-outer annulus fibers tear [ 27 ], allowing herniation of nuclear material into the outer annular structure as a contained protrusion, and part of the disc pass into the vertebral canal space as an extrusion, as shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, adjacent spinal levels become hypermobile as a compensating measure and may stretch and stress the joint capsules. 38,39 Keeping this mechanism in mind, it is possible that the pain-generating facet joint may not be at the level of most severe degeneration, but at the adjacent segments. [40][41][42] This principle is suggested in a prospective outcome study pertaining to lower back pain, which found that 38% to 50% of patients reported having positive outcomes after a facet joint block.…”
Section: Introductionmentioning
confidence: 99%